Reliability and validity of urinary nerve growth factor measurement in women with lower urinary tract symptoms. Issue 8 (30th July 2015) - Vijaya, Gopalan; Cartwright, Rufus; Bhide, Alka; Derpapas, Alexandros; Fernando, Ruwan; Khullar, Vik
Abstract : Introduction and Hypothesis: The validity and reliability of measurement of urinary NGF as a diagnostic biomarker in women with lower urinary tract dysfunction (LUTD) is uncertain. We aimed to evaluate both the diagnostic and discriminant validity, and the test–retest reliability of urinary NGF measurement in women with LUTD. Methods: Urinary NGF was measured in women with LUTD (n = 205) and asymptomatic subjects (n = 31). Urinary NGF was assayed using an ELISA method and normalized against urinary creatinine. NGF/creatinine ratios were compared between symptom subgroups using Mann–Whitney U test, and between different urodynamic diagnoses using the Kruskal–Wallis test. Receiver Operator Characteristic (ROC) analysis was employed to evaluate the diagnostic performance of urinary NGF. Test–retest reliability of NGF measurement was assessed using intra‐class correlation (ICC). Results: Urinary NGF was significantly but non‐specifically increased in symptomatic patients when compared to controls (13.33 vs. 2.05 ng NGF/g Cr, P < 0.001). On multivariate logistic regression NGF was a good predictor of patients having OAB or not, however, the adjusted odds ratio only 1.006. ROC analysis demonstrated poor discriminant ability between different symptomatic groups and urodynamic groups. Using a cut off of 13.0 ng NGF/g creatinine the test provides a sensitivity of 81%, but a specificity of only 39% for overactive bladder. The assays demonstrated good test‐retest reliability with ICC of 0.889. Conclusions: Although urinary NGF can be reliably assayed, and is increased in various LUTDs, it discriminates poorly between these disorders therefore has very limited potential as a biomarker. Neurourol. Urodynam. 35:944–948, 2016 . © 2015 Wiley Periodicals, Inc.